DETERMINATION OF PROTEIN CONTENT AND FRACTION OF CRUDE PROTEIN ANTIGEN CYSTICERCUS CELLULOSAE FROM LOCAL ISOLATE - Nugraha, Leksana Aditya Kris; Swacita, Ida Bagus Ngurah; Apsari, Ida Ayu Pasti (Buletin Veteriner Udayana, 2019)
Cysticercosis is a parasitic disease caused by tapeworm larvae, called Cysticercus. Cysticercus found in pigs is Cysticercus cellulosae which is the larvae of the tapeworm Taenia solium . The purpose of this study was to determine the levels and fractions of Crude protein antigen C. cellulosae . C. cellulosae used is local isolates obtained from infected pigs originating from Karangasem - Bali. Determination of protein content larvae were performed using an Invitrogen Quibit Fluorometer and determination of protein fractions larvae techniques using SDS-PAGE electrophoresis. The results showed that levels of the protein C. cellulosae from local isolate was 867 µg/ml. As for protein fractionation obtained 6 bands protein with a molecular weight: bands 1 = 120.5 kDa, bands 2 = 99.8 kDa, bands 3 = 60.8 kDa, bands 4 = 47.7 kDa, bands 5 = 35.6 kDa, and bands 6 = 23.3 kDa.